The Effectiveness of Play Therapy: Coloring Against Anxiety Reduction in Pre-School Children Who Experience Hospitalization - Nurjanah, Suci; Santoso, Shelfi Dwi Retnani Putri (Universitas Aisyah Pringsewu, 2021)
Hospitalization for children has long-term and short-term impacts. The short-term is fear and anxiety, and if do not treat immediately, the children will deny the care and treatment. The other short-term impacts are insomnia, crying and afraid of the health team, so they deny the treatment given, which will affect the length of stay, aggravate the condition and even cause death. Anxiety causes physiological responses such as changes in the cardiovascular system and gasping breath patterns. Fear and anxiety are disturbances in the emotional needs of children, which requires treatment immediately because it affects their growth and development. The research design used was a quasi-experimental design with